Student Linguistic and Nonlinguistic Problems in Learning the English Speaking - Romlah Ulfaika; Yeremia Ronald Pratama (ELITE Association Indonesia, 2023)
ABSTRACTThere are some non-language factors which indicate that students have the difficulty in speaking and give an impact on the scholars' overall performance in speaking. This study investigated the problem of students in linguistic and nonlinguistic problems in learning the English speaking at the eighth grade students in Tarakan. This research used mixed methods. In this study, the researcher chose the entire class of VIII grade as a sample which consisted of 285 students. In collecting data, researcher used observation, interview and questionnaires as research instruments. Researcher used three main phases in analyzing research data, namely data reduction, data presentation, and verification of conclusion drawing. From the data analysis, the researcher found students in linguistic and nonlinguistic problems and the causes of problems in learning the English speaking, namely the problem of English speaking skills faced by students in the linguistic were lack of vocabulary (61%), poor grammar (69%) and poor pronunciation (64%). Because of these problems, students are reluctant to speak English in class. Furthermore, from the non-linguistic aspect, the problems faced by students were fear of making mistakes (65%), lack of confidence (67%) and fear of evaluation from teachers and friends (63%). Based on some finding, it can be concluded that the biggest cause of student problems in speaking English was fear and lack of confidence to speak English in class. Keywords: Linguistic, nonlinguistic, speaking